Key challenges in Malawi's paprika supply chain: new insights into contract farming. Issue 2 (17th February 2018) - Repar, Lana A.; Onakuse, Stephen; Bogue, Joe; Afonso, Ana
ABSTRACT: Contract farming is a vital tool for linking small-scale farmers with modern supply chains. This study explored challenges resulting from contracting in the paprika supply chain in Malawi. The study used focus groups, semi-structured interviews, and email correspondence with 100 supply chain participants. The identified challenges include: inadequate input provision via the contract, a lack of opportunities to bargain and participate in contract design, and side-selling. While the contract secured the outlet for paprika, it failed to provide a reliable paprika supply for the contracting company. Thus, Malawi's case analyses the potential of contract farming to champion the development of vulnerable economies.